2014
DOI: 10.4103/1319-2442.132205
|View full text |Cite
|
Sign up to set email alerts
|

BK virus-associated hemophagocytic syndrome in a renal transplant recipient

Abstract: Hemophagocytic syndrome (HPS) is a life-threatening hematological disorder in immunocompromised patients. Reactive HPS is observed in patients with systemic infection, neoplasia or auto-immune diseases. It is a rare hematological disorder after renal transplantation and must be suspected when fever and pancytopenia are seen in association with viral infections. HPS is usually associated with infection with the Cytomegalovirus and Epstein-Barr viruses. We report here a case of BK-virus-associated HPS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 0 publications
0
6
0
5
Order By: Relevance
“…Emmenegger et al reported a 59% response with 1.6 g/kg IVIG for 3 days in patients with different Fever (> 38ºC for at least 7 days) Cytopenia affecting 2 or 3 cell types (hemoglobin < 9.0g/dL; neutrophils < 1.000/mm³; platelets < 100.000/mm³) underlying conditions (infection, malignancy, and systemic lupus erythematosus), confirming the effectiveness of this therapeutic strategy, especially with the infectious condition (78% versus 39%). 5,10,12,15,17 The main predictive factor of good clinical response was starting therapy within 2 days of serum ferritin peak. 5,15 Asci et al reported that of the 13 patients with post-KTx HLH analyzed in their study, 6 recovered and received IVIG therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Emmenegger et al reported a 59% response with 1.6 g/kg IVIG for 3 days in patients with different Fever (> 38ºC for at least 7 days) Cytopenia affecting 2 or 3 cell types (hemoglobin < 9.0g/dL; neutrophils < 1.000/mm³; platelets < 100.000/mm³) underlying conditions (infection, malignancy, and systemic lupus erythematosus), confirming the effectiveness of this therapeutic strategy, especially with the infectious condition (78% versus 39%). 5,10,12,15,17 The main predictive factor of good clinical response was starting therapy within 2 days of serum ferritin peak. 5,15 Asci et al reported that of the 13 patients with post-KTx HLH analyzed in their study, 6 recovered and received IVIG therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Pancytopenia or severe neutropenia associated with BKV infection have been found in kidney transplant recipients[ 284 - 286 ]. Hemophagocytic syndrome was diagnosed in one of these patients[ 286 ].…”
Section: Clinical Manifestations Of Bkv Infection Other Than Nephropamentioning
confidence: 99%
“…Secondary HPS was first described at 1979 in 19 patients interestingly, thirteen of of these patients were renal transplant recipients. In transplant recipients, HPS often triggers by an infection, mainly viral, including adenovirus, human herpes virus 8 (HHV-8), Epstein-Barr virus (EBV), cytomegalovirus (CMV) ( 12 , 13 ), HHV-6 ( 14 ), parvovirus B19 ( 15 , 16 ) and BK polyomavirus ( 17 ), herpes viruses account for 62% of viral cases of HPS, and EBV is known as the most prominent of them ( 2 ). Tuberculosis, toxoplasmosis, leishmaniosis, babesiosis, Rickettsia spp, and Staphylococcus spp and Escherichia coli have been reported as the causative infections triger for initiation and development of HPS ( 18 - 20 ) .…”
Section: Mechanisms and Diagnostic Criteriamentioning
confidence: 99%